Eficiência energética aplicada à instituição de ensino público - RIBEIRO, Patrick da Silva (2019)
This study has as main objective to analyze the energy use of a federal public educational institution, and from this provide measures aimed at the efficient use of electricity. To achieve this purpose load surveys were conducted in each sector of the institution, and from these data were estimated consumption values the same. This estimate was made necessary by the fact that the institution does not have electricity metering system. From the energy consumption analysis waste were verified and presented actions that aimed the use of efficient and con-scious of this energy, thus resulting in significant economic values, resulting in 15.30% annu-al reduction in energy consumption.